Information Technology in Bio- and Medical Informatics 4th International Conference, ITBAM 2013, Prague, Czech Republic, August 28, 2013. Proceedings - Bursa, Miroslav; Khuri, Sami; Renda, M. Elena (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2013)
This book constitutes the refereed proceedings of the 4th International Conference on Information Technology in Bio- and Medical Informatics, ITBAM 2013, held in Prague, Czech Republic, in August 2013, held in conjunction with DEXA 2013. The 7 revised long papers presented together with 4 short papers were carefully reviewed and selected from numerous submissions. The papers address the following topics: critical health and intelligent systems in medical research, and obstetrics, neonatology and decision systems in cardiology.